Hepatic Damage Induced By Fructose And Aspartame In Carbonated Drinks: Morphological And Histological Analysis In Adult Male Albino Rats - Shafqat, Faiza; Suhail, Muhammad; Ali, Ayesha; Nazeer, Hafsa; Iqbal, Sadia; Mansoor, Saqib (Journal of Rawalpindi Medical College, 2024)
Objective: The study aims to analyze the changes produced by fructose and aspartame in regular and zero-calorie carbonated drinks respectively on the morphology and histology of the liver of adult male albino rats. Methods: Regular and zero-calorie carbonated drinks in a dosage of 10 ml/kg body weight were administered by oral gavage daily to experimental groups B and C (10 rats in each group) respectively for 21 consecutive days. The weight of animals was noted at the start and end of the experiment. The liver was excised in each animal, weighed, fixed in formalin, and stained with Hematoxylin and Eosin and histological changes such as detachment of capsule, congestion and inflammation of portal triad were observed for comparison between the experimental groups. Results: Results were recorded and analyzed in the form of photomicrographs. Observations showed a rise in the weight of animals and liver of experimental groups B and C compared to control group A. The shape of the liver was normal. Histological changes including detachment of capsule, inflammation of portal triad, congestion of hepatic sinusoids and portal triad, were observed in both the experimental groups indicating damage to hepatic tissue. Conclusion: Therefore, it is concluded that consumption of regular and zero-calorie carbonated drinks should be restricted to avoid their harmful effects on the liver leading to hepatotoxicity. Keywords: Fructose, Aspartame, regular and zero calorie carbonated drinks, liver